Protein engineering of an oxidative cleavage-free pathway for crocetin-dialdehyde production in Escherichia coli - Lee, Jun Ho; Park, Jeong Yang; Seo, Min Duk; Lee, Pyung Cheon (Metabolic Engineering, 2025)
The growing depletion of petroleum resources and the increasing demand for sustainable alternatives have spurred advancements in microorganism-based biofactories. Among high-value compounds, carotenoids are widely sought after in pharmaceuticals, cosmetics, and nutrition, making them prime candidates for microbial production. In this study, we engineered an efficient biosynthetic pathway in Escherichia coli for the production of the C20-carotenoid crocetin-dialdehyde. By bypassing traditional oxidative cleavage reactions mediated by carotenoid cleavage dioxygenases (CCDs), our approach reduces the enzymatic complexity of the pathway. Using the crystal structure of a CrtMLIKE enzyme identified in this study, we developed a mutant enzyme capable of condensing two C10-geranyl pyrophosphate molecules to form C20-phytoene. This intermediate was then desaturated and oxidized by CrtN and CrtP to produce crocetin-dialdehyde, achieving a yield of 1.13 mg/L. By reducing enzyme requirements from six to three and eliminating the need for CCDs, this pathway alleviates metabolic stress on the host and enhances the scalability of production for industrial applications. Overall, our research presents a streamlined and innovative approach to carotenoid biosynthesis, advancing sustainable production methods for short-chain carotenoids.
Keywords: Biofactories; Carotenoid cleavage dioxygenase; Crocetin; Dialdehydes; Dioxygenases; Microbial production; Oxidative cleavages; Petroleum resources; Protein engineering; Proteins structures; Carotenoids; Dioxygenases; Escherichia coli; Escherichia coli Proteins; Metabolic Engineering; Oxidation-Reduction; Protein Engineering; Vitamin A; Carotenoid cleavage dioxygenases; Crocetin; Metabolic engineering; Protein engineering; Protein structure